Defensive Regurgitation by a Noctuid Moth Larva (Litoprosopus Futilis) - Scott R. Smedley; Elizabeth Ehrhardt; Thomas Eisner (Psyche: A Journal of Entomology)
Larvae of the noctuid moth Litoprosopus futilis regurgitate when disturbed. The oral effluent proved deterrent to ants on nearcontact, and topically irritating in a scratch test with a cockroach. Larvae regurgitated when attacked by lycosid spiders and derived some protection from this behavior. Caterpillars were able to regurgitate even when emerging from the eggs; however, at this stage, they proved vulnerable to attack by chrysopid larvae and ants.